2020
DOI: 10.3389/fpls.2020.578631
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth as a Source of Antihypertensive Peptides

Abstract: Amaranth is an ancestral crop used by pre-Columbian cultures for 6000 to 8000 years. Its grains have a relevant chemical composition not only from a nutritional point of view but also due to the contribution of components with good techno-functional properties and important potential as bioactive compounds. Numerous studies have shown that amaranth storage proteins possess encrypted sequences that, once released, exhibit different physiological activities. One of the most studied is antihypertensive activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 121 publications
0
16
0
2
Order By: Relevance
“…This class of drugs act by inhibiting the release of renin, the conversion of angiotensin I to angiotensin II via inhibition of angiotensin-converting enzyme (ACE) and/or blocking of angiotensin receptors (AR), especially angiotensin receptor-1 (AR-1) and mineralocorticoid receptor (MR) that interact with angiotensin II to promote aldosterone secretion [ 136 ]. Several natural products are currently being explored as potential anti-hypertensive agents, including plant-polyphenols and protein-derived peptides [ 137 , 138 , 139 ]. Hydrolysates of lupin proteins exhibited potential anti-hypertensive effects in an in vitro set-up by inhibiting ACE activity with IC 50 value of 226 µg/mL [ 4 ].…”
Section: Biological Activities Of Ldpsmentioning
confidence: 99%
“…This class of drugs act by inhibiting the release of renin, the conversion of angiotensin I to angiotensin II via inhibition of angiotensin-converting enzyme (ACE) and/or blocking of angiotensin receptors (AR), especially angiotensin receptor-1 (AR-1) and mineralocorticoid receptor (MR) that interact with angiotensin II to promote aldosterone secretion [ 136 ]. Several natural products are currently being explored as potential anti-hypertensive agents, including plant-polyphenols and protein-derived peptides [ 137 , 138 , 139 ]. Hydrolysates of lupin proteins exhibited potential anti-hypertensive effects in an in vitro set-up by inhibiting ACE activity with IC 50 value of 226 µg/mL [ 4 ].…”
Section: Biological Activities Of Ldpsmentioning
confidence: 99%
“…The food value of 100g of amaranth oil is noted in Table 1. Notably, compared to cereal alternatives, the grain has more proteins, lipids, and minerals [46]. It is rich in antioxidants and phytochemicals, and has previously been shown to have antihypertensive, antidiabetic, and anticholesteremic effects [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, amaranth contains bioactive peptides [46,[62][63][64]. Previous researchers found amaranth derived peptides and tetrapeptides with ACE-inhibitory activity Functional Food Science 2021; 1(10):39-49 [65][66][67] Previously, it has been shown that curcumin decreased proteinuria levels [35], but such data with amaranth oil has not been presented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations